Pengaruh Kualitas Pelayanan Kesehatan Pasien Rawat Inap Di Ruangan Kelas Terhadap Kepuasan Pasien Pada RSUD Dr. Doris Sylvanus Kota Palangka Raya: The Influence of the Quality of Health Services for Patients Hospitalized in the Classroom towards Patient Satisfaction at the RSUD Dr. Doris Sylvanus, Palangka Raya - Pahlawan, Reza; Bestria, Bestria (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2016)
This study aims to determine the Quality of Health Services for Inpatients in Classrooms given by the RSUD dr. Doris Sylvanuskota Palangka Raya, to find out patient satisfaction with the services provided by RSUD dr. Doris Sylvanus, Palangka Raya city, to find out how much the influence of the quality of health services for patients hospitalized in the classroom towards patient satisfaction at the RSUD dr. Doris Sylvanus in Palangka Raya City. The method used in this study is the Associative Quantitative method. Data collection techniques use questionnaires (questionnaires). The number of samples in this study were 340 people. The sampling technique in this study is a simple random sampling method, which is a random sampling technique regardless of the strata in the population. The results of the analysis using Pearson ProductMoment Correlation can get value of rxy by 0.9870. This shows that the quality of health care for inpatients in the classroom provides a significant positive effect on patient satisfaction in Dr. Doris Sylvanus Hospital. Judging from the tangible indicator has a significant positive effect on product quality indicators consisting of health facilities. Indicator of reliability has a significant positive effect on service quality indicators which consist of service guarantees. Indicators of responsiveness have a significant positive effect on emotional indicators, namely psychological reactions. The assurance indicator has a positive effect on the price indicator, which is price match.